Desain Dan Implementasi Sistem Informasi Manajemen Presensi PT.XYZ Menggunakan Metode Agile - Jerry Brilianto Akbar; Nizirwan Anwar (Prosiding SISFOTEK, 2024)
This study aims to develop a more efficient and accurate presence management information system at PT Silicaindo. Agile methodology is used to ensure that the developed system is responsive to changes in user needs. The process begins with an in-depth analysis of user needs, which are then implemented into a system design using UML, flowcharts, and wireframes. The developed system is then tested using black-box testing to ensure optimal functionality. After testing, the system is handed over to PT Silicaindo for implementation. User feedback is collected during the review stage, which allows for further system improvements and enhancements. Finally, the system is launched and ready to be used by all employees of PT Silicaindo. This study successfully demonstrates how agile methods can be applied to develop complex and dynamic systems, resulting in systems that are stable, functional, and in accordance with user needs.